Analyte focusing by micelle collapse for liquid extraction surface analysis coupled with capillary electrophoresis of neutral analytes on a solid surface. Issue 18 (4th June 2019) - Jeong, Sunkyung; Shakerian, Farid; Chung, Doo Soo
Abstract: Liquid extraction surface analysis (LESA) has an advantage of directly sampling analytes on a surface, thus avoiding unnecessary dilution by homogenization of the bulk sample commonly practiced in solid sample analysis. By combining LESA with CE, the additional advantage of separating analytes before detection can be accomplished. For neutral molecules, MEKC needs to be used. Since the detection sensitivity of CE in general suffers from the small capillary dimension, analyte focusing by micelle collapse was employed for enhanced extraction in LESA and sample preconcentration for MEKC. In addition, using a commercial CE instrument, the LESA process was performed much faster and more reliably compared to our first demonstration of LESA‐CE using a homemade CE setup. Three neutral water‐insoluble pesticides sprayed on an apple skin were directly extracted, preconcentrated, and analyzed by the automated LESA‐analyte focusing by micelle collapse‐MEKC with high sensitivity in 10 min. The relative standard deviations of the migration times and peak heights were 0.8–2.1 and 1.2–3.0%, respectively when ametryn was used as an internal standard. The limits of detection obtained with UV absorbance at 200 nm were 1.8–6.4 ppb.